Does adherence to the World Cancer Research Fund/American Institute of Cancer Research cancer prevention guidelines reduce risk of colorectal cancer in the UK Women's Cohort Study?. Issue 3 (21st January 2018) - Jones, Petra; Cade, Janet E.; Evans, Charlotte E. L.; Hancock, Neil; Greenwood, Darren C.
Abstract: Evidence on adherence to diet-related cancer prevention guidelines and associations with colorectal cancer (CRC) risk is limited and conflicting. The aim of this cohort analysis is to evaluate associations between adherence to the World Cancer Research Fund/American Institute of Cancer Research (WCRF/AICR) 2007 recommendations and incident CRC. The UK Women's Cohort Study comprises over 35 372 women who filled in a FFQ at baseline in 1995. They were followed up for CRC incidence for a median of 17·4 years, an individual score linking adherence to eight of the WCRF/AICR recommendations was constructed. Cox proportional hazards regression provided hazard ratios (HR) and 95 % CI for the estimation of CRC risk, adjusting for confounders. Following exclusions, 444 CRC cases were identified. In the multivariate-adjusted model, women within the second and third (highest) categories of the WRCF/AICR score had HR of 0·79 (95 % CI 0·62, 1·00) and 0·73 (95 % CI 0·48, 1·10), respectively, for CRC compared with those in the lowest, reference category. The overall linear trend across the categories was not significant ( P =0·17). No significant associations were observed between the WCRF/AICR score and proximal colon, distal colon and rectal cancers separately. Of the individual score components, a BMI within the normal weight range was borderline significantly protective only for rectal cancer in the fully adjusted model. In view of the likely different causes of CRC subtypes, further research is needed to identify the optimal dietary patterns associated with reducing colon and rectal cancer risk, respectively.